Perbandingan Pendapatan Usaha Pengolahan Gula Kelapa Cetak dan Gula Kelapa Semut di Kecamatan Dawan Kabupaten Klungkung - WAHYUNI, DESAK AYU KOMANG SRI; AMBARAWATI, I GUSTI AGUNG AYU; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.2, Desember 2023, 2023)
Comparison of Business Income of Molded Coconut Sugar Processing and Coconut Sugar Ants in Dawan District, Klungkung Regency.  Dawan Village and Besan Village are two villages located in Dawan District, Klungkung Regency which have a lot of palm sugar and ant industries. Coconut sugar has a higher selling price due to product certification and differences in quality. The purpose of this study was to determine the income comparison and to find out the constraints faced by craftsmen from the business of processing coconut sugar and coconut sugar in Dawan District, Klungkung Regency. The research was conducted from July to September 2020 with a survey method, namely direct interviews with craftsmen. The total population is 39 molded coconut sugar craftsmen and 20 ant coconut sugar. The samples used were 20 craftsmen each. Determination of the sample method is done by probability sampling with a simple. random sampling technique The analysis used is income analysis and t , which is to find out the comparison of printed coconut sugar income with ant coconut sugar. The data analyzed includes income in one year, namely 2019. The results of the study are based on income analysis, namely the income of printed coconut sugar craftsmen in a year is Rp. 23,570,162/business. Coconut sugar craftsmen have an income of Rp 40,602,774/business. The income of molded coconut sugar craftsmen compared to ant coconut sugar is Rp 17,032,612/business in one year. Comparison income coconut sugar ant higher that is equal to 72%. Based on the results of the t there is a significant difference in income between the molded coconut sugar business and the ant coconut sugar business. The obstacles faced by the craftsmen are raw materials, capital,availability of tapping and marketing personnel.